"Bursting" to Go and Other Experiences: Children's Views on Using the Toilet in the First School Year. (June 2017) - Tatlow-Golden, Mimi; O'Farrelly, Christine; Booth, Ailbhe; Doyle, Orla
Children's use of the toilet at school, although rarely explored, is an important facet of school experience with consequences for physical and psychological health. A mixed methods study investigated views of 25 children (4–5 years) regarding potential stressors in the first school year, including views of toileting, in Dublin, Ireland. Despite very positive responses to school, most responses to toileting (15 of 25) were mixed or negative. Although some liked to go, or noted the toilets were clean, most indicated delayed toilet use ("bursting" to go) and ambivalent or negative experiences such as fear of not identifying the right toilet, fear of being alone, lack of privacy, and potential bullying. Many children did not expect to receive help from the teacher. As delaying toilet use can have lasting health consequences, teacher–nurse collaboration could be used to develop whole-school policies to support children's early adjustment in this sensitive area of functioning.